Effect of Urochloa brizantha density on competition with Myracrodruon urundeuva - Murilo Antônio Oliveira Ruas; Leonardo David Tuffi Santos; Luan Mateus Silva Donato Donato; José Ângeles Moreira de Oliveira Oliveira; Victor Augustus Vasconcelos de Oliveira; Rodinei Facco Pegoraro (Bioscience Journal)
Cultivating Myracrodruon urundeuva seedlings in forest restoration or intercropped areas is significantly challenging due to the competition with weeds, especially forage grasses. This study evaluated the influence of Urochloa brizantha density on the initial growth, physiological response, and macronutrient utilization of M. urundeuva seedlings. The experiment used randomized blocks with six replications. It included different densities of the U. brizantha competitor, where 0 (control), 14, 28, and 42 individuals/m² corresponded to 0, 1, 2, and 3 competitor plants per pot, respectively. U. brizantha competition reduced the photosynthetic rate (> 35%), water use efficiency (> 23%), and shoot dry mass (> 24%) of M. urundeuva compared to the controls. U. brizantha also affected M. urundeuva’s P and K absorption more than other macronutrients. Regardless of competitor density, the coexistence of U. brizantha influences the photosynthesis, water use, and macronutrient absorption, especially P and K, by M. urundeuva, providing lower biomass of the tree species. The U. brizantha competitor, grown at low densities, stimulated root growth, height gain, and the accumulation of N, S, and Mg in the shoot, as well as all macronutrients in M. urundeuva roots.